Continuous forests and non-IBA forest patches provide a safe haven for the tropical bird community in highly fragmented urban landscapes - Sharifah Nur Atikah; Yahya, Muhammad Syafiq; Ong, Kang Woei; Sanusi, Ruzana; Norhisham, Ahmad Razi; Md Sharif, Badrul Azhar (Springer Science and Business Media, 2025)
One of the primary anthropogenic activities driving the shrinking of tropical forests is urban development, which often results in the formation of fragmented forest areas surrounded by diverse human-modified landscapes. Isolation and fragmentation of natural habitats have been linked to a variety of detrimental effects on ecosystems and biodiversity. Currently, there is limited information on how urban forest fragmentation affects avian communities in tropical regions. Our study investigated the impacts of habitat fragmentation on bird community assemblages in four forest patches and in one continuous forest within rapidly developing Greater Kuala Lumpur, Malaysia. Using point count sampling method, we recorded 4,144 bird encounters spanning 196 resident and migratory species, nearly 60% of which are experiencing global population decline. Our findings show that continuous forests can support greater avian diversity than fragmented forests. We also found that bird community assemblages differed significantly amongst forest types, with continuous forest having the most distinct bird community and highest species evenness. Our study further identified the value of retaining urban forests as habitats and biological corridors for resident birds and as stopover sites for migratory birds, including rare, threatened, or endangered species (RTE). Maintaining existing urban forest areas is therefore crucial for the conservation of bird species, both at a local and global level. This can be further enhanced by incorporating these forests into Important Bird and Biodiversity Area (IBA) networks in the region.